Are Brazilian cities ready to develop an efficient urban freight mobility plan? - Dias, José Maria; Sobanski, Gabriel Bugan; Silva, João Eduardo Azevedo Ramos da; Oliveira, Leise Kelli de; Vieira, José Geraldo Vidal (Revista Brasileira de Gestão Urbana, 2018)
According to the Urban Mobility National Policy (UMNP), Brazilian cities with more than 20,000 inhabitants are obligated to elaborate Urban Mobility Plans (UMPs). The literature shows a lack of national research on urban freight planning and a need for better understanding issues on cargo transportation for authorities, especially regarding decision-making on policies and on urban freight transportation planning. City Logistics solutions can be considered on UMPs to reduce the problematic urban freight transport. Therefore, a survey was applied to investigate the resources available within cities to draw UMPs, the solutions for cargo movement in Brazilian cities, and the perceptions of public managers about freight transportation. The results show that “restrictions” are the solutions most adopted by Brazilian authorities, including the representative sample for cities within the São Paulo State with more than 250,000 inhabitants. The conclusions point out that Brazilian cities are not prepared to develop an efficient urban freight plan, as public managers seem to be unconscious about urban logistics demands within their cities or have neglected aspects regarding urban freight within the UMNP.